Understanding Acid and Base Concepts among Chemistry and Biology Pre-service Teachers at Faculty of Education in Amran University–Yemen - Al-Hadabi, Abdulsalam Sulaiman Dawood (Arab Journal for Sciences and Research Publishing, 2016)
This study aimed to find out Yemeni chemistry and biology pre-service teachers' (YCBPSTs) understanding of acid and base concepts. To this end, a cross sectional study was conducted on a sample consisted of 246 subjects that were selected from 590 of CBPSTs enrolled in the preparation program of science pre-service teachers (SPSTs) at faculty of education-Amran university in Yemen. An acid-base test, 24 multiple-choice questions, was developed as an instrument to carry out this study. Content validity as well as reliability of the instrument were calculated. Cronbach alpha coefficient of the instrument was found to be (0.72). Results of this study revealed that the overall scores of all participants were low. Hence the percentages of the average scores achieved on the overall acid-base test and its scales for all participants were respectively (38%, 40%, 36%, and 36%). In addition, it was found that no statistical significant difference in the mean of achievement scores on the test in all groups' comparisons except for the ones that dealt with the academic year. Based on results of the study, it was recommend to widen its scope by conducting different studies that explore the YCPSTs’ understanding of other chemistry concepts in different program preparation of YCPSTs.
Keywords: Science Education; Chemistry Education; Chemistry Concepts; Chemistry Pre-service Teachers; Biology Pre-service Teachers